2013
DOI: 10.4049/jimmunol.1202445
|View full text |Cite
|
Sign up to set email alerts
|

Differential Binding of Pyruvate Dehydrogenase Complex-E2 Epitopes by DRB1*08:01 and DRB1*11:01 Is Predicted by Their Structural Motifs and Correlates with Disease Risk

Abstract: DRB1*08:01 (DR0801) and DRB1*11:01 (DR1101) are highly homologous alleles that have opposing effects on susceptibility to primary biliary cirrhosis (PBC). DR0801 confers risk and shares a key feature with other HLA class II alleles that predispose to autoimmunity: a non-aspartic acid at beta57. DR1101 is associated with protection from PBC and its sequence includes an aspartic acid at beta57. To elucidate a mechanism for the opposing effects of these HLA alleles on PBC susceptibility we compared the features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…The opposing effects of DRB1*0801 and DRB1*1101 in our study show the same direction of effect as those reported in a study of PBC, which is a condition associated with cognitive impairment [Newton et al, ; Hollingsworth et al, ; Chow et al, ]. PBC is an autoimmune liver disease where 53% of patients have moderate to severe problems with concentration and memory that are not correlated with histological and biochemical markers of disease severity [Newton et al, ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The opposing effects of DRB1*0801 and DRB1*1101 in our study show the same direction of effect as those reported in a study of PBC, which is a condition associated with cognitive impairment [Newton et al, ; Hollingsworth et al, ; Chow et al, ]. PBC is an autoimmune liver disease where 53% of patients have moderate to severe problems with concentration and memory that are not correlated with histological and biochemical markers of disease severity [Newton et al, ].…”
Section: Discussionsupporting
confidence: 83%
“…DRB1*0801 and DRB1*1101 have previously been associated with a number of conditions including juvenile idiopathic arthritis (JIA) [Massa et al, ], multiple sclerosis (MS) [Qiu et al, ], systemic lupus erythematosus [Graham et al, ; Castaño‐Rodríguez et al, ], type 1 diabetes [Petrone et al, ; Erlich et al, ; Muixí et al, ], and PBC [Donaldson et al, ; Chow et al, ]. In the latter three conditions, DRB1*1101 has been reported to be a protective allele and DRB1*0801 has been the susceptibility allele.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found a portion of the epitopes restricted to more than one HLA allele. For example, M1 232–244 and M1 240–252 , although reported to be restricted to DRB5 and DQ1, respectively (29), were found in our study to be presented by DPB1*0501 (Figures 4C,D); NP 409–421 restricted to DRB1*12:02 (Figure 5B) was once reported to be restricted to DRB1*15:01 (IEDB) and DRB1*08:01 (26), etc. These results further confirmed that many CD4 + T cell epitopes may be presented by multiple HLA molecules (Table 1).…”
Section: Discussionsupporting
confidence: 40%
“…A few previously reported epitopes were among the ones we identified in this study, such as M1 105–117 , NP 102–114 , and NP 463–475 . However, some of these such as M1 33–52 , M1 228–244 , NP 102–114 , and NP 409–421 were reported to be restricted to different HLA-II molecules; for example NP 409–421 peptide restricted to DRB1*0801 rather than here DRB1*1202 (26). Moreover, M1 240–252 restricted to DPB1*0501, was identified as a highly conserved epitope among strains of H1N1, H3N2, and even H5N1 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Although these possibilities require further investigation, recent exciting work has shown that T cells with the risk-conferring HLA DRB1*08:01 genotype shown high-affinity responses to specific pyruvate dehydrogenase E2 subunit peptides, response that did not develop in the presence of the protective DRB1*11:01 allele [56].…”
Section: The Hla Gene Variants Associated With Pbcmentioning
confidence: 99%